Armed drones: can civilians be protected? - Šniutė, Vincas; Šniutė, Danas (Vilnius University Open Series, 2020)
Armed drone is a military technology that is being used not only for surveillance but also in combat operations. In some military operations the distinctive technological features of drones offer an advantage compared to manned aircraft. Most of the military operations which are conducted by drones fall under Protocol Additional to the Geneva Conventions of 12 August 1949 and Relating to the Protection of Victims of Non-International Armed Conflicts (Protocol II). The use of military drones in non-international armed conflicts causes many legal problems in the international humanitarian law, concerning the protection of civilians. Nevertheless, armed drones are legal under international humanitarian law. The most relevant principles of international humanitarian law concerning the use of armed drones are distinction and proportionality. These principles can be fulfilled more effectively by drone operators because of the advanced technology of drones. However, the use of armed drones in real life operations usually violate the international humanitarian law and its core principles. Thus, existing regulation cannot protect the lives of civilians. Additional regulation of armed drones at the UN level could create international legal mechanism which would protect the civilians. However, the current political situation, as well as the difficult decision-making procedures at the UN institutions, suggest that future legal regulation is not likely to be enacted anytime soon.